2007
DOI: 10.1128/aac.00478-06
|View full text |Cite
|
Sign up to set email alerts
|

Human β-Defensins Kill Candida albicans in an Energy-Dependent and Salt-Sensitive Manner without Causing Membrane Disruption

Abstract: Human ␤-defensin 2 (hBD-2) and hBD-3 have potent fungicidal activity in the micromolar range. Although little is known about their mechanism of action against Candida species, some similarities to the antifungal mechanism of salivary peptide histatin 5 (Hst 5) seem to exist. Since hBD-2 and hBD-3 have been reported to cause direct disruption of target cell membranes, we compared the effects of hBD-2 and hBD-3 on Candida albicans membrane integrity. Incubation of calcein-loaded C. albicans cells with a dose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
101
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(110 citation statements)
references
References 33 publications
9
101
0
Order By: Relevance
“…Taken together, therefore, the data suggest that caspofungin at concentrations below the MIC causes C. albicans cells to undergo apoptosis but that increasing caspofungin concentrations above the MIC does not further induce programmed cell death responses. Previous studies have shown that several stimuli, including acetic acid (7), hydrogen peroxide (27), 1,10-phenanthroline metal complexes (28), silver-coumarin complexes (17), diallyl disulfide (29), farsenol (26), lactoferrin (30), defensins (31), and the antifungal agent amphotericin B (9), cause C. albicans cells to undergo apoptosis. Our data demonstrate that cell wall stress stemming from inhibition of (1,3)-␤-D-glucan, as caused by caspofungin and Zymolyase (at concentrations Ն0.1 mg/ml), is also a trigger for apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, therefore, the data suggest that caspofungin at concentrations below the MIC causes C. albicans cells to undergo apoptosis but that increasing caspofungin concentrations above the MIC does not further induce programmed cell death responses. Previous studies have shown that several stimuli, including acetic acid (7), hydrogen peroxide (27), 1,10-phenanthroline metal complexes (28), silver-coumarin complexes (17), diallyl disulfide (29), farsenol (26), lactoferrin (30), defensins (31), and the antifungal agent amphotericin B (9), cause C. albicans cells to undergo apoptosis. Our data demonstrate that cell wall stress stemming from inhibition of (1,3)-␤-D-glucan, as caused by caspofungin and Zymolyase (at concentrations Ն0.1 mg/ml), is also a trigger for apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…They do not seem to cause gross membrane disruption in C. albicans (21), and a moderate membrane permeabilization has been reported only for hBD-3 (21,12).…”
mentioning
confidence: 99%
“…Human ␤-defensins 2 and 3 (hBD-2 and hBD-3) display potent in vitro activity against C. albicans (11,10,21), but their antifungal mechanism is poorly understood. They do not seem to cause gross membrane disruption in C. albicans (21), and a moderate membrane permeabilization has been reported only for hBD-3 (21,12).…”
mentioning
confidence: 99%
“…Salivary histatin 5 induces fungal cell death via the release of cellular ATP and activation of P2X receptors (13), in a process that involves an interaction with cell wall proteins (14) and a potassium channel (15). Human beta-defensins display some shared mechanisms with histatin 5, yet synergy between some beta-defensins and histatin 5 indicates that not all targets are shared (16). The human cathelicidin LL-37 acts via disruption of the plasma membrane.…”
mentioning
confidence: 99%